PENGARUH EMPLOYEE ENGAGEMENT DAN WORK VALUE TERHADAP JOB HOPPING KARYAWAN GENERASI MILLENNIAL PADA GOLDEN TULIP JINENG RESORT BALI - Sianturi, Nathania Reandra; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
The phenomenon of job moving for a short period, known as job hopping, has become a common practice among millennials with a variety of reasons. Golden Tulip Jineng Resort Bali is one of the tourism industries which has been experiencing the job hopping phenomenon. This study aims to determine the effect of employee engagement and work value to job hopping phenomenon on millennial employees at Golden Tulip Jineng Resort Bali. This is an explanatory research and the sampling uses nonprobability sampling techniques, that is purposive sampling method. Data collection used are physical questionnaires directly sent to the employees . The sample was 40 respondents who are considered as millennial employees working in food&beverage and front office division. This study uses quantitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression. The results of multiple linear regression analysis show that there was a positive effect of employee engagement and work value to job hopping which indicate an increasing independent variables would impact an increasing dependent variable. The variable correlation coefficient of both independent variables to dependent variable has a strong relationship. The determination coefficient of employee engagement worths 49,8% and the determination coefficient of work value employee worths 36,4% indicate both independent variable are capable of describing and predicting dependent variable’s variation. By the output obtained through SPSS, the company is advised to conduct more bonding activities in order to strengthen relationship between the co-workers itself also with the boss. The company could also attempts to fullfil the values which are considered important by the employees.